2011
DOI: 10.1111/j.1447-0594.2011.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of household composition and required care level with functional and cognitive status among disabled Japanese elderly living in a suburban apartment complex

Abstract: It is important for health-care providers to assess in detail the status of the disabled elderly considering both their household composition and care level in planning and providing assistance for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…They also suggested that unmarried elderly people living only with their children had significantly greater disability than those in other living arrangements. Murayama et al [6] reported that functional and cognitive conditions were associated with household composition, especially among elderly people living alone. The present study did not analyze in detail the family members’ characteristics and living conditions for elderly subjects who lived with family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that unmarried elderly people living only with their children had significantly greater disability than those in other living arrangements. Murayama et al [6] reported that functional and cognitive conditions were associated with household composition, especially among elderly people living alone. The present study did not analyze in detail the family members’ characteristics and living conditions for elderly subjects who lived with family.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number of elderly people living alone and those living only with a spouse has significantly increased, and several risks have been identified for this age-group [5,10,11]. Household composition is an important factor when assessing needs and providing health-care services for elderly people, and it includes the physical, mental, and social functional conditions of such people as well as their caregivers [6,12]. However, few reports have examined the relationship between these diverse household factors related to the elderly and their functional disability.…”
Section: Introductionmentioning
confidence: 99%
“…Severe cognitive impairment is clinically diagnosed as dementia ( Hugo and Ganguli, 2014 ). At the same time, with the accelerated aging of the population, there are increasingly more empty nesters and those living alone ( Murayama et al, 2012 ). While traditional family care functions are gradually weakening ( Ng et al, 2002 ), an increasing number of the elderly tend to choose the mode of community home-based care.…”
Section: Introductionmentioning
confidence: 99%
“…The number of elderly persons in the population is increasing, especially in developed countries 1) . In 2015, the proportion of individuals aged 65 and above was 8.5% of the global population; however, this percentage is expected to increase to 17% by 2050.…”
Section: Introductionmentioning
confidence: 99%